Pemikiran Pendidkan Ibnu Khaldun dan Implementasinya dalam Dunia Kontemporer - Roisah Maulidiyah Rohmah; Siti Rahmatul Rizkiyah; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2024)
Ibn Khaldun's thought in Islamic education philosophy emphasizes the importance of knowledge and education as the main elements in the formation of civilization. This article aims to explore the concept of education according to Ibn Khaldun in the philosophy of Islamic education, especially in relation to the moral, intellectual, and social development of individuals. The method used is a literature review through the analysis of Ibn Khaldun's works, especially Muqaddimah. The results showed that Ibn Khaldun viewed education as a gradual process that requires a balance between theory and practice, as well as the importance of the teacher's role in shaping student character. In conclusion, Ibn Khaldun's concept of education is relevant in the context of modern education, because it emphasizes the importance of the relationship between moral and intellectual education. This article aims to explore Ibn Khaldun's thoughts on education in an Islamic perspective, especially how education affects the development of social and civilization.